Meningkatkan Keterampilan Berbicara Siswa melalui Pattern Drill Technique - Ambarsari, Lies (Neolectura, 2023)
The objective of this research was to describe the process of improving students’ speaking skill, to explore and clarify a phenomenon in social reality, especially to know how the teacher improves students’ speaking skill through pattern drill technique. This research was done at SMK BPS&K II Bekasi using Class Action Research based on descriptive data to improve students’ speaking ability which was taken sample of 25 eleventh grade students using speaking tests, interviews, observation and documentations of students’ activities while research was running in the class. The research was done by four steps in every cycle; they were planning, acting, observing and reflecting. The research scored the students’ speaking ability through pronunciation, grammar, vocabulary, fluency and comprehension. Based on the Classroom Action Research done by the researcher, it has shown that the eleventh grade students of SMK BPS&K 2 Bekasi have made increase in speaking English. In cycle 1, the researcher got data from 25 students and the score was 1824 with average score 72, 96. At the cycle 2, their score increased be 1924 with average score 76, 88 and at the cycle 3, final presentation from 25 students have gotten score 2018 and the average score was 80, 72. The conclusion from the observation from Cycle 1 to Cycle 3 was that using Pattern Drill Technique proven improved students’ speaking English. The implementation of pattern drill technique used by the researcher was very appropriate for students at the eleventh grade, because they were more active to speak up in class. The repetition technique promoted students who were still difficult to arrange the sentences. The questions given to them stimulated their mind in mastering some vocabularies to speak up during speaking and learning activities. Their enthusiasms were high and they were confident to improve their speaking ability.